A case of spontaneous arm levitation in progressive supranuclear palsy - AĞAN YILDIRIM, KADRİYE (SPRINGER-VERLAG, 2000)
Progressive supranuclear palsy is one of the parkinsonial syndromes causing atypical parkinsonism. In recent reports, other than subcortical involvement, also cortical structures have been shown to be involved in progressive supranuclear palsy patients. One of the clinical presentations of this involvement is spontaneous arm levitation which is a component of alien limb syndrome. Here we report a clinically diagnosed progressive supranuclear palsy patient with spontaneous arm levitation. Clinically spontaneous levitation of one arm without denial of ownership suggests the presence of spontaneous arm levitation. Spontaneous arm levitation can occur in the setting of progressive supranuclear palsy and it possibly demonstrates the cortical involvement in this disorder.
Keywords: progressive supranuclear palsy; alien limb; arm levitation; DEGENERATION